Pengelolaan dan Penginputan Data Sektor Perkebunan sebagai Pendukung Program Satu Data di Dinas Perkebunan Provinsi Sumatera Selatan - Reva Azzahra Triana; Imamulhakim Syahid Putra (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Sectoral data management plays a vital role in supporting data-driven governance, particularly through the implementation of the ‘One Data Indonesia’ policy. This article aims to describe the processes of data management and data entry for the plantation sector at the South Sumatra Provincial Plantation Office in support of the ‘One Data South Sumatra’ Programme. This study employs a qualitative descriptive approach, utilising data collection techniques such as direct observation and documentation. The findings indicate that the data management process involves several stages: checking the list of data requirements, verifying data availability, inputting available data into the ‘Satu Data’ portal, and documenting issues regarding data that is not yet available or finalised. Of the six key indicators requested, four are already available: the percentage increase in the production of rubber, coconut, oil palm and coffee. Meanwhile, the other two indicators—the area under plantation development and the percentage of plantation infrastructure development realised—are not yet available. Furthermore, some supporting data are still provisional figures for 2025 and therefore require further verification before they can be used as final data. These findings indicate that the success of sectoral data management is determined not only by the data input process, but also by data availability, clarity of data status, validation, and coordination between data producers and data custodians.